2023
DOI: 10.3390/jpm13020203
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to the Implementation of Personalised Medicine across Europe

Abstract: (1) Background: Personalised medicine (PM) is an innovative way to produce better patient outcomes by using an individualised or stratified approach to disease and treatment rather than a collective approach to treating patients. PM is a major challenge for all European healthcare systems. This article aims to identify the needs of citizens in terms of PM adaptation, as well as to provide insights into the barriers and facilitators categorised in relation to key stakeholders of their implementation. (2) Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, there is still a gap in the collection of genetic or genomic information due to the limited genomic infrastructure in hospitals. The findings of this study are consistent with the existing literature, where limited clinical data on the determinants of diseases and limited availability of genetic data, as well as complex logistics, were reported as barriers hindering the integration of PM into cancer treatment [30][31][32]. In fact, Erdman et al reported that a lack of sufficient genetic, environmental, and lifestyle information is a barrier to implementing PM [33].…”
Section: Patient Datasupporting
confidence: 89%
“…However, there is still a gap in the collection of genetic or genomic information due to the limited genomic infrastructure in hospitals. The findings of this study are consistent with the existing literature, where limited clinical data on the determinants of diseases and limited availability of genetic data, as well as complex logistics, were reported as barriers hindering the integration of PM into cancer treatment [30][31][32]. In fact, Erdman et al reported that a lack of sufficient genetic, environmental, and lifestyle information is a barrier to implementing PM [33].…”
Section: Patient Datasupporting
confidence: 89%
“…These statements are important evidence of what the field itself perceives as significant determinants of the present conditions. In the article "Personalised Medicine barriers facilitators healthcare systems" Stefanicka-Wojtas and Kurpas explore the needs, barriers, and facilitators of implementing Personalized Medicine (PM) in European healthcare systems [63]. The barriers for the implementation of precision medicine are categorized into seven areas of need and ten key stakeholders.…”
Section: Determining Factors In Pcmmentioning
confidence: 99%
“…These statements are important evidence of what the field itself perceives as significant determinants of the present conditions. In the article “Barriers and Facilitators to the Implementation of Personalised Medicine across Europe”, Stefanicka-Wojtas and Kurpas explore the needs, barriers, and facilitators of implementing personalized medicine (PM) in European healthcare systems [ 74 ]. The barriers for the implementation of precision medicine can be categorized into three main factors (policy, organizational, and economic) and six key stakeholders (patient, authorities, policy makers, funding agents, industry, and academia).…”
Section: Determining Factors In Pcmmentioning
confidence: 99%